Penfolds - Calkins, Tim (SAGE Knowledge. Cases., 2017)
The Penfolds case is designed to help students think through brand positioning and brand portfolio questions. Penfolds, one of the world's best known brands of wine, is performing poorly and a new management team needs to quickly reverse the business trends. To do so, the new management team needs to answer key questions, such as: What is Penfolds' positioning? Has the brand extended too far? Can Penfolds successfully play in all price segments of the wine industry? What is the best way to grow the brand going forward?